COVID-19 as crisis-induced innovation lab - Torfing, Jacob; Bentzen, Tina Øllgaard; Jensen, Didde Cramer (Politica, 2022)
Against a tragic background, this study shows that the COVID-19 pandemic has catalyzed positive innovations in both welfare solutions as well as in public governance solutions of the Danish public sector. Drawing on qualitative as well as quantitative data, this article outlines the character and perceived effects of new welfare solutions among vulnerable citizens, as well as a number of preceding, organizational changes in the administrative machinery of the public sector. Based on this analysis, we generate and discuss a hypothesis about a possible relationship between the governance and welfare innovations that emerged during COVID-19.